Human trafficking and the modern slavery framing of the problem: Between rhetorical pathos and conceptual limitations - Petrova, Donka (Cognition, Communication, Discourse, 2022)
Trafficking in human beings is a serious problem, which affects vulnerable groups disproportionately. Eastern European countries are among the most affected due to a variety of risk factors. Yet this problem often remains invisible to the mass public. The attempts to bring it into the public consciousness rely strongly on different rhetorical strategies. I argue that the way of social issue framing largely determines its public perceptions and reactions to it. This material examines human trafficking as phenomenon, its definitions and root causes, and then focuses on the framing of trafficking as modern slavery. This framing is made possible by the use of multimodality in media outlets and in prevention campaigns. I will apply the method of content analysis of images used in the Bulgarian digital press or for campaign purposes. The combination of text and imagery is a powerful tool to create the association of slavery, detention, and captivity. These associations are emotionally contagious and can generate pathos; they also convey the idea of a powerless innocent victim in need of rescue, which is a limiting view. The paper argues that this approach has both its positive and negative aspects, the latter being the risks of reductiveness and barriers to the deeper understanding of the problem, its underlying causes, and possible solutions. The alternative framing of this phenomenon as a human rights violation implies the necessity of not just “rescue and salvation” of individuals, but also structural changes in society.